Pengaruh Keaktifan Berorganisasi Terhadap Prestasi Akademik Mahasiswa Biologi Universitas Islam Negeri Sumatera Utara - Nur Afinni, Ummi; Fadilla, Audia; Syamsia , Zia; Purnama, Fadlya (Comit: Communication, Information and Technology Journal, 2024)
Higheri educationi isi ani importanti stagei ini ai student'si life,i wherei theyi arei expectedi toi acquirei thei necessaryi knowledgei andi skillsi toi achievei academici success.i Thei purposei ofi writingi thisi journali isi toi determinei thei effecti ofi beingi activei ini organizations,i toi findi outi thei factorsi thati influencei thei activenessi ofi organizingi Biologyi studentsi at UIN-SU and to find out that there is a relationship between organizational activity and academic achievement of Biology students at UIN-SU. This study uses a quantitative descriptive research method. The sampling technique is Random Sampling. The sample in this study were 19 Tadris Biology students at UIN-SU. Data collection techniques are through tests and non-tests. The tests are in the form of description questions to measure symbolic abilities, as well as students' understanding of "The Influence of Organized Activeness on Academic Achievement of Biology Students at the State Islamic University of North Sumatra". Non-test techniques in the form of questionnaires and closed interviews, namely using the Google Form. The benefits obtained from being active in the organization apart from the influence on academic achievement are adding many useful relationships and increasing a sense of responsibility and good teamwork and adding new experiences that are not obtained in college lessons, and also affecting ourselves for example skill development public speaking, can develop self-potential, train sensitivity to the surrounding environment and increase a sense of concern for others as well as fostering productive, innovative, creative and critical abilities. Keywords: Organized Activeness, Student Academic Achievement